Designing and evaluating a psychological intervention for individuals with Multiple Complex Needs - Sapsford, Hayley (2021)
Multiple Complex Needs refers to any two of the following: homelessness, substance misuse, offending behaviour and/or mental health difficulties. Personal agency is compromised within those who experience difficulties in their mental health, impacted on further by adversity and disempowerment. The Power Threat Meaning Framework (PTMF) has been designed by its authors to take disempowerment in psychological suffering into account and provide a narrative to make sense of experiences and regain a sense of personal agency. The lack of systematic and empirical evidence for the PTMF provides further reason to conduct research within this area and explore its use. This research aimed to design a brief intervention based on the PTMF and explore the outcomes, utility and feasibility with adults experiencing Multiple Complex Needs (MCN).